I Act Therefore I Live? Autopoiesis, Sensorimotor Autonomy, and Extended Agency: (Diametros, 2025)
This paper aims to determine whether extended human-machine cognitive systems and group systems can be regarded as autonomous agents. For this purpose, I compare two notions of agency: one developed within analytical philosophy of action and based on the concept of intention, and the other introduced by enactivists via the concepts of autopoiesis and sensorimotor autonomy. I argue that only the latter approach can be used to demonstrate autonomous agency in respect of systems that are not humans as such, though they contain humans as their elements. After introducing Maturana and Varela’s conception of minimal autonomy as a kind of generalization of autopoiesis, I present the three conditions of agency put forward by Barandiaran, Di Paolo and Rohde, noting that they do not invoke the property of being alive as necessary in that respect. I argue that both extended and group systems can satisfy these conditions of agency, even though they are not alive as such. The fulfillment of these conditions, however, is ensured by the autopoietic nature of the living components of these systems. That being said, an autonomous system itself does not need to be alive in the biological sense. Sensorimotor, adaptive agency could emerge out of other processes than those responsible for biological life. The article concludes with a suggestion that this is exactly what will happen if an autonomous system is ever artificially created. It would be functionally indistinguishable from a living organism, though not alive in a biological sense.
Keywords: autopoiesis; agency; extended cognitive system; group system; sensorimotor autonomy; enactivism